2009
DOI: 10.1038/ejhg.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intrafamilial communication of hereditary breast and ovarian cancer genetic information

Abstract: What factors influence intrafamilial communication of hereditary breast and ovarian cancer (HBOC) genetic risk information? Such information can have health implications for individuals who undergo genetic testing, but it can also have implications for their blood relatives. This literature review adopts an ecological model to summarize factors at the individual, familial, and community levels, as well as cross cutting factors relating to the complexity of HBOC genetic information and responsibilities that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 37 publications
6
55
0
Order By: Relevance
“…The literature has overwhelmingly shown that women tend to be considered the “kin keepers” of family health history and as such, are seen as the responsible ones for disseminating health information within the family (Foster, Eeles, Ardern-Jones, Moynihan, & Watson, 2004; Koehly et al, 2009; Nycum, Avard, & Knoppers, 2009; Wiseman, Dancyger, & Michie, 2010). The findings from this study suggest that women's beliefs about cancer may be influenced by whether or not they have a family history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has overwhelmingly shown that women tend to be considered the “kin keepers” of family health history and as such, are seen as the responsible ones for disseminating health information within the family (Foster, Eeles, Ardern-Jones, Moynihan, & Watson, 2004; Koehly et al, 2009; Nycum, Avard, & Knoppers, 2009; Wiseman, Dancyger, & Michie, 2010). The findings from this study suggest that women's beliefs about cancer may be influenced by whether or not they have a family history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This raises ethical issues for health professionals and services, as their degree of responsibility for ensuring relatives' awareness of their risks -and the extent to which they should be proactive in this task -have long been debated in genetic health care. 16,17 Previous reviews have been published on the process and outcomes of communication of genetic information within families, [18][19][20] including the communication between children and their parents, 21 the factors influencing patterns of intrafamilial communication and awareness, 22,23 and on the analysis of the communication between genetic specialists and patients. 24 However, to our knowledge there has been no systematic review of studies that have analysed how family communication of information about genetic risks is addressed in genetic counselling practice.…”
Section: Introductionmentioning
confidence: 99%
“…While most studies and reviews report an overall adjustment in the first couple of years post predictive testing, [5][6][7][8] distress levels may start to rise again later, presumably as the time approaches to possible disease onset. 9 Further, individuals may experience difficulties in specific areas of their lives such as family communication 10,11 and discrimination at home and in the work place or with insurance. 12 How young adults choosing to test early cope with such challenges and to what extent pretest counselling provides adequate support and preparation, has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%